2010
DOI: 10.1089/jop.2010.0076
|View full text |Cite
|
Sign up to set email alerts
|

A Cationic TAT Peptide Inhibits Herpes Simplex Virus Type 1 Infection of Human Corneal Epithelial Cells

Abstract: Purpose: To determine if a peptide, TAT-Cd 0 , inhibits Herpes simplex virus type 1 infection of human corneal epithelial cells. Methods: TAT-Cd 0 and a control peptide, E 50,51 TAT-Cd 0 , were added at various times throughout infection with the lacz-expressing hrR3 virus, and viral replication was measured by b-galactosidase activity. Toxicity was assessed using a dye reduction assay. Results: The CC 50 value for TAT-Cd 0 was *100 mM. In assays with peptide present at all times, TAT-Cd 0 was 150-fold more ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The antiviral activity of TAT-Cd 0 is not cell type dependent, and the peptide has been shown to have low cytotoxicity in culture and in a murine eye model. 15,16 TAT-Cd 0 also inactivates virus in solution (EC 50 ¼ 34 lM) and treatment of cells prior to infection can make them resistant to infection (EC 50 ¼ 0.4 lM). 14 Based on these properties, TAT-Cd 0 has the potential to be an effective antiviral with alternative mechanisms of action compared with currently available drugs.…”
Section: Results Tat-cdmentioning
confidence: 99%
“…The antiviral activity of TAT-Cd 0 is not cell type dependent, and the peptide has been shown to have low cytotoxicity in culture and in a murine eye model. 15,16 TAT-Cd 0 also inactivates virus in solution (EC 50 ¼ 34 lM) and treatment of cells prior to infection can make them resistant to infection (EC 50 ¼ 0.4 lM). 14 Based on these properties, TAT-Cd 0 has the potential to be an effective antiviral with alternative mechanisms of action compared with currently available drugs.…”
Section: Results Tat-cdmentioning
confidence: 99%
“…148 A cationic steroid antibiotic (CSA)-13 that is proposed to mimic the activity of endogenous AMPs can inhibit Acanthamoeba trophozoite growth without significant toxicity to mouse fibroblast cells. 219 The cationic Peptide TAT-Cd0 can reduce the ability of HSV-1 to infect human corneal epithelial cells 220 and reduce the severity of keratitis, delay the onset of vascularisation and stromal keratitis, reduce the percentage of mice presenting with disease and viral titres. 221 However, treatment needed to be early in the disease process (four hours after initiation of infection) for these effects to be seen.…”
Section: Evidence For Effectiveness Of Antimicrobial Peptides To Treat Ocular Infectionsmentioning
confidence: 99%
“…They are being synthesized and used as inhibitors against HSV infections 127 . The TAT (transactivator of transcription)-peptide, derived from HIV, has been shown to inhibit infection of HSV in the in vitro and in vivo models of HSV infections 128 129 . A study showed the effect of a synthetic 3-OS HS specific peptide: G2 in blocking HSV-2 infections in human cervical (HeLa) cell lines.…”
Section: Treatment and Preventionmentioning
confidence: 99%